2020
DOI: 10.1002/jsfa.10691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variety, storage container, and duration on the physical properties, oil content, germination capacity, and seed loss due to Plodia interpunctella infestation of Ethiopian sesame

Abstract: BACKGROUNDOwing to fluctuations of international market prices and excess supply during peak harvesting seasons, farmers and traders often suffer from a low market price of sesame. Such a negative impact can be ameliorated by taking advantage of times with a better market price during the off season. This study aimed to investigate the impact of different storage containers on gravimetric properties and germination capacities of five different sesame varieties as well as their impact on Indian meal moth (Plodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This was consistent with Mendoza et al [ 23 ] and Walker et al [ 24 ], who found that the moisture content of maize increased significantly during conventional storage. However, both PICS and SGP bags maintained sesame seed moisture within the safe storage range of 6-8% throughout the storage period [ 25 ], indicating a lack of exchanges between hermetic bags and the outside environment. These findings are consistent with the findings of various studies that have demonstrated the efficacy of hermetic bags [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was consistent with Mendoza et al [ 23 ] and Walker et al [ 24 ], who found that the moisture content of maize increased significantly during conventional storage. However, both PICS and SGP bags maintained sesame seed moisture within the safe storage range of 6-8% throughout the storage period [ 25 ], indicating a lack of exchanges between hermetic bags and the outside environment. These findings are consistent with the findings of various studies that have demonstrated the efficacy of hermetic bags [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other two non-hermetic storage bags, on the other hand, did not significantly contribute to oxygen depletion, and the evolution of carbon dioxide and level were close to atmospheric levels throughout all assessment periods. This could be due to the bags’ lack of hermetic conditions, which likely facilitated gaseous exchange between the outside environment and the inside of the bags during storage [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the product is infected, the carcasses, excrements, and other secretions of these pests become mixed with it. The product’s germination rate, nutritional value, quality, and safety level will be seriously reduced; thus, P. interpunctella has caused great economic losses in the United States, China, Korea, Ethiopia, and in other countries [ 9 , 10 , 11 , 12 ]. Due to it being a generalist feeder with a heterogeneous diet and high ability to damage food products, this pest has become the focus of the world for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Sesame is an important food source and oil crop in the world. 1,2 In addition to being widely used in food, about 50% of sesame is used for processing into sesame oil. 3 Sesame oil contains many lignans, vitamin E, plant sterols, and other active substances [4][5][6] with antioxidant properties, [7][8][9] and anti-cancer and anti-aging effects.…”
Section: Introductionmentioning
confidence: 99%
“…Sesame is an important food source and oil crop in the world 1,2 . In addition to being widely used in food, about 50% of sesame is used for processing into sesame oil 3 .…”
Section: Introductionmentioning
confidence: 99%